Student Perceptions of Team-Based Learning in the Criminal Justice Classroom. Issue 3 (2nd July 2020) - Craig, Jessica M.; Nodeland, Brooke; Long, Roxanne; Spivey, Emily
Abstract: As instructors seek ways to increase student engagement and retention, several innovative pedagogical approaches have been developed that fosters critical thinking and quality group work. One of these approaches is Team-Based Learning (TBL), a flipped-classroom model that has been found to improve student outcomes and knowledge retention. While prior research has found students tend to have positive perceptions of TBL, these have been limited to other disciplines. The current study sought to examine how students perceive the use of TBL in two criminal justice courses through pre- and post-test surveys. Results indicated that students overall had positive perceptions of TBL as they found solving problems in teams to be effective and tended to prefer TBL to traditional lecture-based courses. Implications and future directions are also discussed.